Pelatihan Pembuatan Laporan Keuangan Sederhana Sebagai Upaya Peningkatan Pengetahuan Pengelolaan Keuangan pada Pelaku Usaha Mikro - Khariidatul Bahiyyah; Lala Nurhidayat; Bella Prillia Hania (Universitas Perjuangan Tasikmalaya, 2026)
Pabrik Tahu Sukasari is one of the micro enterprises in Ciamis Regency that has not yet implemented a structured financial recording system. All transactions are still recorded manually, making it difficult for the business owner to determine production costs and the financial position of the business. This community service activity aims to assist the owner in understanding and preparing simple financial statements according to operational needs. The training was conducted online using a participatory method, which included explanations on the importance of bookkeeping, practical transaction recording, and evaluation through pre-test and post-test. The results show an increase in participants’ understanding, from an initial score of 40 to 90 after the training. This activity resulted in an increased understanding of financial management and awareness of the importance of financial record-keeping for the sustainability of micro enterprises.